(untitled) (Global Journal of Management and Business Research, 2020)
Supply chain management is one of the biggest challenges of today when it is crucial to remain active in the market and competitive without compromising the processes within the company itself. The costs of production and living in general are increasing day by day and it is up to the management of the company to reduce costs to the lowest possible level in order to maintain profitability in the market. In this paper we address the issue of the supply chain and forecasting method. The impact of supply chain management extends beyond reducing costs (Farris II